EUROPEAN REMIT REGULATION AS THE LATEST DETERMINANT OF CORPORATE RISK MANAGEMENT STRATEGIES IN ENERGY SECTOR - Mykhailo Rushkovskyi; Dmytro Rasshyvalov (Green, Blue and Digital Economy Journal, 2022)
The purpose of the paper is to summarize and present the fundamental trends of the past few decades related to the financial crisis of 2008 and growing integration of European sovereign economies, including the integration of energy markets, that led to development of regulation of relationships and preventing manipulation in such markets. This regulation has become a powerful new determinant for the European multinational enterprises of the energy sector (MNE) when developing their own risk management strategies. Methodology. The analysis is based on the recent studies of the pan-European power exchange company Nord Pool Group, international organization Energy Community and relevant regulations and recommendations of the European Parliament and of the Council and European Union Agency for the Cooperation of Energy Regulators. Results of the analysis showed the growing demand for transparency and stability in the European wholesale energy markets. This demand was reflected in the EU Regulation 1227/2011 on Wholesale Energy Market Integrity and Transparency (REMIT) that was adopted by the European Parliament and the Council of the EU in 2011. While REMIT Regulation, on one hand, provides reliable and equal conditions for MNE, on the other hand, it increases the risk and burden of REMIT compliance obligations for such MNE. The consequences of misconduct can potentially be serious – both high fines and personal liability of MNE employees. Today the European multinational enterprises of the energy sector must develop the respective risk management strategies to ensure effective governance of this type of risks. Practical implications. MNE participants of the EU energy market should develop efficient risk management strategies to comply with REMIT requirements, in addition to existing commitments on the transparency of the Third Package. The REMIT compliance risk management strategies will support MNE market participants in complying with rules and policies, creating a secure structure for employees of such enterprises and promoting fair and equal conditions for trade, trusting the energy market. Furthermore, proper REMIT compliance risk management strategy will help to avoid or minimize the risk of fines and other regulatory sanctions and potential civil lawsuits. It will also help to avoid or minimize the risk of reputation loss, such as negative media reviews or poor customer experience. Value/originality. The conducted analysis provides deep understanding of the main drivers of the European wholesale energy markets regulations that create a compelling determinant for the risk management strategies of multinational enterprises of the energy sector. Ukraine has committed itself to the Energy Community to implement the REMIT Regulation in its regulatory field, which increases the relevance of developing appropriate multinational enterprises risk management strategies within the country.